Family Affair? Long-Term Economic and Mental Effects of Spousal Cancer - Petri Böckerman; Mika Kortelainen; Henri Salokangas; Maria Vaalavuo (Institute of Labor Economics (IZA), 2023)
Emerging strands of research have examined the family spillover effects of health shocks, usually focusing on labour market outcomes. However, the results have been inconclusive and there is only little evidence on the longer term consequences of health shocks or the mechanisms behind the spillover effects. We analyse the short- and long-term effects of cancer on the healthy spouse's labour supply and mental health by gender and relative income status within the couple (i.e., the breadwinner type). We use full population register data on all cancer patients and their cohabiting partners in Finland over the period 1995-2019. Our identification strategy is based on the quasi-random variation in the timing of the cancer diagnosis and a dynamic difference-in-differences approach. We find two main results. First, cancer increases female spouses' employment. This result is consistent with the added worker effect, although we find the magnitude of the increase in annual earnings to be negligible. By contrast, among male spouses, earnings decrease as a consequence of a spouse's cancer. Second, among women, there is heterogeneity in the effects in terms of the breadwinner status, which is especially notable in the long-term. The results show that the added worker effect is visible only among secondary earners and the effect seems to hold only when the cancer patient dies. Secondary earner women also suffer more from psychiatric symptoms during bereavement. Consequently, we argue that the breadwinner status before the health shock is a neglected factor influencing the effects of health shocks in families, and that family-level specialisation between spouses alters substantially over time in response to a health shock.
Keywords: I10; J12; J17; J22; 330; health shock; cancer; family spillover effects; employment; earnings; household division of labour; event study; difference-in-differences